2009
DOI: 10.1007/s10616-009-9240-x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human lung cancer cell growth and migration by berbamine

Abstract: The purpose of this study is to investigate the effects of berbamine (BER), a naturally occurring small-molecule compound from Traditional Chinese Medicine (TCM) Berberis amurensis, on the growth and migration of human lung cancer A549 cell line. This cell line is the non-small cell lung cancer (NSCLC) which constitutes 80% of lung cancer cases and remains an aggressive lung cancer associated with a poor patient survival. Our present results have shown that BER significantly suppressed the in vitro and ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 19 publications
(19 reference statements)
2
15
0
Order By: Relevance
“…We found that ␤-catenin and Stat3 were present in a protein complex immunoprecipitated by the CaMKII ␥ antibody (Figure 7E-F). These findings, together with previous studies, 25,26 unravel that CaMKII ␥ is a critical molecular switch which could activate multiple LSC-related signaling networks including Wnt/␤-catenin, Stat3, and NF-B pathways.…”
Section: Camkii ␥ Is a Critical Target Of Berbamine For Its Antileukesupporting
confidence: 70%
See 1 more Smart Citation
“…We found that ␤-catenin and Stat3 were present in a protein complex immunoprecipitated by the CaMKII ␥ antibody (Figure 7E-F). These findings, together with previous studies, 25,26 unravel that CaMKII ␥ is a critical molecular switch which could activate multiple LSC-related signaling networks including Wnt/␤-catenin, Stat3, and NF-B pathways.…”
Section: Camkii ␥ Is a Critical Target Of Berbamine For Its Antileukesupporting
confidence: 70%
“…At the cellular level, berbamine exhibits significantly antiproliferative activities of a variety of leukemia, [17][18][19][20][21] lymphoma, 22 multiple myeloma, 23 and solid tumor cell lines. [24][25][26][27] At the molecular level, berbamine-mediated antitumor activity was shown to be involved in PI3K/Akt, 22 nuclear factor kappaB, 23 Fas-mediated apoptosis, 26 calmodulin, 28,29 phospholipase A2, 16,30,31 P-glycoprotein, 24 and telomerase activity. 32 A previous study showed that compound E6, an analog of berbamine, can inhibit calmodulin-dependent myosin light chain kinase (MLCK) activity through affecting calmodulin (CaM) but not MLCK.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed procedures were followed accordingly (Duan et al 2009). In brief, hepatoma cells at 70% confluence were treated for 48 h with perifosine at concentrations of 0 (DMSO, vehicle as control) and 10 lmol/L, respectively.…”
Section: Morphological Evaluation Of Apoptotic Cellsmentioning
confidence: 99%
“…The balance between these two groups plays a critical role in regulating cell growth and controlling mitochondrial membrane integrity (Basanez et al 2001;Duan et al 2010;Luan et al 2010;Zhang et al 2009). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%